Negative electrode material, positive electrode material, negative electrode plate, positive electrode plate, battery and preparation method

By using COF/MOF composite materials as negative electrode materials and graphene/graphite composite materials as positive electrode materials in sodium-based dual-ion batteries, the problems of poor conductivity, safety issues and capacity attenuation in the existing technology are solved, and high-energy density and high power density battery performance.

CN119361620APending Publication Date: 2025-01-24中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411177796.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The positive and negative electrode materials of existing sodium-based dual-ion batteries have problems such as poor conductivity, safety problems and capacity attenuation, which are difficult to meet the needs of high energy density and high power density.

Method used

COF/MOF composite materials are used as negative materials and graphene/graphite composite materials as positive poles, and the structural stability and conductivity of the material are improved through specific preparation methods.

Benefits of technology

It significantly improves the energy density and power density of the battery, solves the problem of safety problems and capacity attenuation of metal branches, and improves the magnification, cycle performance, and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361620A_ABST
    Figure CN119361620A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a negative electrode material, a positive electrode material, a negative plate, a positive plate, a battery and a preparation method. The negative electrode material is a COF / MOF composite material; comprising an MOF core body and a COF layer coated on the surface of the MOF core body. COF / MOF with high conductivity and good chemical stability is used as a negative electrode material, the modified graphene / graphite composite material is used as a positive electrode and is assembled with the electrolyte and the diaphragm, the process is simple and safe, the conductivity is high, and the rate capability, the cycle performance and the energy density are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically relates to a negative electrode material, a positive electrode material, a negative electrode sheet, a positive electrode sheet, a battery and a preparation method thereof. Background Art

[0002] With the development of science and technology, batteries are being used more and more widely. Dual-ion batteries are a new type of battery. Both the positive and negative electrodes use active materials, which can store and release ions, thereby realizing the conversion and storage of electrical energy. Unlike traditional rocking-chair batteries that rely on the migration of a single cation between the positive and negative electrodes to store energy, in the process of charging and discharging, anions and cations are embedded in the positive and negative electrodes respectively, and participate in the energy storage process at the same time. The high potential of anions embedded in the positive electrode can provide high energy density for dual-ion batteries. The coordinated embedding of anions and cations and the rapid ion migration enable dual-ion batteries to achieve high power density.

[0003] Sodium has a high theoretical specific capacity and a low electrode potential. Currently, there are several types of positive and negative electrode materials for preparing sodium-based dual-ion batteries: the first is graphite, but the larger ion size and abnormal Na-C formation energy make the graphite negative electrode only provide less than 30mA h / g of sodium storage, and the conductivity is poor, which is obviously not applicable to sodium-based dual-ion batteries; the second is the metal negative electrode, which uses alloying reactions and uses the metal as both the negative electrode and the negative electrode current collector of the battery. This negative electrode metal sheet effectively improves the energy density of the battery, such as tin metal, but when the metal reaches a fully sodiumized state, its volume expansion rate reaches 420%, which will cause the SEI film to rupture, thereby aggravating the occurrence of side reactions and causing safety problems. The above have an impact on the performance of dual-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a negative electrode material, a positive electrode material, a negative electrode sheet, a positive electrode sheet, a battery and a preparation method.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A negative electrode material is a COF / MOF composite material; it comprises a MOF core and a COF layer coated on the surface of the MOF core.

[0007] The MOF is one of NH2-UiO-66, NH2-MIL-101(Fe), or ZIF-8.

[0008] The COF layer is prepared from 4-formylphenylboric acid and 1,3,5-tri(4-aminophenyl)benzene; preferably, the mass ratio of 4-formylphenylboric acid to 1,3,5-tri(4-aminophenyl)benzene is 3:1-3.5:1; preferably 3:1.

[0009] The present invention also includes a method for preparing the negative electrode material, comprising the following steps: 1) preparing a MOF precursor; preferably, the preparation is carried out in the following manner: adding an M salt and a ligand to a solvent, and collecting a centrifugal product after the reaction; preferably, the M salt is one of a Zr salt, an Fe salt, and a Cu salt; the ligand is one of phthalic acid, 2-aminoterephthalic acid, or 2-methyl-imidazole; the molar ratio of the M salt to the ligand is 1:1-1.5:1; preferably 1:1;

[0010] 2) Add styrene to the MOF precursor to obtain a MOF styrene suspension;

[0011] 3) 4-formylphenylboronic acid and 1,3,5-tri(4-aminophenyl)benzene are added to the MOF styrene suspension and heated for reaction; preferably, the heating temperature is 70-150° C. and the reaction time is 10-24 h;

[0012] 4) After the reaction is completed, the centrifugal product is further heated to obtain the negative electrode material; preferably, the heating temperature is 120° C. and the reaction time is 12 h.

[0013] The present invention also includes a negative electrode sheet, including the negative electrode material, the negative electrode conductor and the negative electrode binder; preferably, the negative electrode conductor is CNT; the negative electrode binder is PVDF; preferably, the mass ratio of the negative electrode material, the negative electrode conductor and the negative electrode binder is 8:1:1.

[0014] The present invention also includes a method for preparing a positive electrode material, which comprises the following steps: 1) placing graphite powder in a tube furnace, heating it to 800-1000° C., and introducing a carbon source gas; preferably, the carbon source gas is methane; the flow rate is 1-3 L / min, and the reaction time is 30-60 minutes, to obtain a graphene / graphite composite material;

[0015] 2) performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension; preferably, the ultrasonic power is 500 W and the ultrasonic time is 2 hours;

[0016] 3) Pour the suspension into a high temperature furnace, heat to 1500-2000°C, maintain the pressure at 0.5-1atm, and heat treat for 1-2 hours to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 800-1000°C for 1-5h to obtain a positive electrode material.

[0017] The present invention also includes a positive electrode material which is a graphene / graphite composite material obtained by the preparation method.

[0018] The present invention also includes a positive electrode sheet, including the positive electrode material, the positive electrode conductor and the positive electrode binder; preferably, the positive electrode conductor is CNT; preferably, the binder is PVDF; preferably, the mass ratio of the positive electrode material, the positive electrode conductor and the positive electrode binder is (96-97):(1-3):(1-3).

[0019] The present invention also includes a battery, including a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte; preferably, the battery is a sodium-based dual-ion battery. Preferably, the negative electrode sheet is the negative electrode sheet obtained by the above preparation method; preferably, the positive electrode sheet is the positive electrode sheet obtained by the above preparation method.

[0020] The present invention also includes a method for preparing the battery, which adopts the following steps: assembling a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator to obtain a battery; preferably, the electrolyte is NaPF6 dissolved in a mixed solution of EC:EMC at a mass ratio of 1:1, and 10wt% FEC is added to obtain the electrolyte.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention optionally uses a COF / MOF composite material as the negative electrode material: the COF / MOF composite material has high structural stability and electronic conductivity, which can effectively improve the energy density and power density of the battery. At the same time, the porous structure of the COF / MOF composite material can provide a large number of active sites, which is conducive to the storage and transmission of electrolytes, and solves the safety problems of metal dendrites and capacity attenuation faced by dual-ion batteries.

[0023] Graphene / graphite composite materials can be used as positive electrode materials: Graphene / graphite has high electrochemical activity and stability, which can effectively improve the energy density and power density of the battery. At the same time, the layered structure of graphene / graphite is conducive to the transmission of electrons, which can further improve the electrochemical performance of the battery.

[0024] As a preferred form, COF / MOF with high conductivity and good chemical stability is used as the negative electrode material, and the modified graphene / graphite composite material is used as the positive electrode and assembled with the electrolyte and the separator. The process is simple and safe, the conductivity is high, and the rate performance, cycle performance and energy density are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 0.5C battery cycle data at 25°C for the examples and comparative examples. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0027] Example 1

[0028] Preparation of positive electrode material: 1) Put graphite powder into a tube furnace, heat to 1000°C, introduce carbon source gas methane at a flow rate of 1 L / min, and react for 30 minutes to obtain a graphene / graphite composite material.

[0029] 2) Performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension, the ultrasonic power is 500 W, and the ultrasonic time is 2 hours.

[0030] 3) Pour the suspension into a high temperature furnace, heat to 2000° C., maintain the pressure at 1 atm, and heat treat for 1 hour to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 1000° C. for 5 hours to obtain the positive electrode material 1.

[0031] Preparation of positive electrode sheet: positive electrode material 1: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain positive electrode sheet 1.

[0032] Preparation of negative electrode materials: 1) Dissolve 169 mg zirconium chloride solution (ZrCl4) and 121 mg 1,4-phthalic acid (H2BDC, with a molar ratio of 1:1 to ZrCl4) in a mixed solution of 28 ml DMF, place in a reactor and heat at 150°C for 12 h, collect the product by centrifugation, and wash it three times with DMF and methanol to obtain NH2-UiO-66MOF precursor.

[0033] 2) Add 50 ml of styrene to the MOF precursor and ultrasonicate for 30 minutes to obtain a MOF suspension. 3) Then add 200 mg of 4-formylphenylboric acid (FPBA) and 150 mg of 1,3,5-tri(4-aminophenyl)benzene (TAPB) in two portions, pour into a reactor, heat at 120°C for 6 hours, and then centrifuge. The obtained product is placed in a tubular furnace and heated at 800°C for 12 hours to obtain a COF / MOF negative electrode material 1 with high conductivity and high active sites.

[0034] Preparation of negative electrode sheet: negative electrode material 1: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 1.

[0035] Preparation of electrolyte: NaPF6 was dissolved in a mixture of EC:EMC at a mass ratio of 1:1, and 10 wt% FEC was added to obtain the electrolyte.

[0036] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 1, negative electrode sheet 1, electrolyte and separator, and assemble the battery. Battery number is 1. Battery 1 is tested for charge and discharge cycles at 25°C, current of 0.5C and voltage of 3.0-4.5V. The test data is shown in Figure 1 .

[0037] Example 2

[0038] Preparation of positive electrode material: 1) Put graphite powder into a tube furnace, heat to 1000°C, introduce carbon source gas methane at a flow rate of 1 L / min, and react for 30 minutes to obtain a graphene / graphite composite material.

[0039] 2) Performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension, the ultrasonic power is 500 W, and the ultrasonic time is 2 hours.

[0040] 3) Pour the suspension into a high temperature furnace, heat to 2000° C., maintain the pressure at 1 atm, and heat treat for 1 hour to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 1000° C. for 5 hours to obtain the positive electrode material 1.

[0041] Preparation of positive electrode sheet: positive electrode material: CNT: PVDF are mixed in a mass ratio of 96:3:1, coated on a current collector, dried, and rolled to obtain positive electrode sheet 2.

[0042] Preparation of negative electrode materials: 1) Dissolve 169 mg zirconium chloride solution (ZrCl4) and 121 mg 1,4-phthalic acid (H2BDC) in a mixed solution of 28 ml DMF, place in a reactor and heat at 150°C for 12 h, collect the product by centrifugation, and wash with DMF and methanol three times to obtain a MOF precursor.

[0043] 2) 50 ml of styrene was added to the MOF precursor and ultrasonicated for 30 minutes to obtain a MOF suspension. 3) 200 mg of 4-formylphenylboric acid (FPBA) and 150 mg of 1,3,5-tri(4-aminophenyl)benzene (TAPB) were added twice, poured into a reactor, heated at 120°C for 6 hours, and then centrifuged. The obtained product was placed in a tubular furnace and heated at 800°C for 12 hours to obtain a COF / MOF negative electrode material 1 with high conductivity and high active sites.

[0044] Preparation of negative electrode sheet: negative electrode material 1: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 1.

[0045] Preparation of electrolyte: NaPF6 was dissolved in a mixture of EC:EMC at a mass ratio of 1:1, and 10 wt% FEC was added to obtain the electrolyte.

[0046] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 2, negative electrode sheet 1, electrolyte and separator, and assemble the battery. Battery number is 2. Battery 2 is tested for charge and discharge cycles at 25°C, current 0.5C, voltage 3.0-4.5V, and test data are shown in Figure 1 .

[0047] Example 3

[0048] Preparation of positive electrode material: 1) Put graphite powder into a tube furnace, heat to 1000°C, introduce carbon source gas methane at a flow rate of 1 L / min, and react for 30 minutes to obtain a graphene / graphite composite material.

[0049] 2) Performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension, the ultrasonic power is 500 W, and the ultrasonic time is 2 hours.

[0050] 3) Pour the suspension into a high-temperature furnace, heat to 2000°C, maintain the pressure at 1 atm, and heat treat for 1 hour to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 1000°C for 5 hours (time, temperature) to obtain positive electrode material 1.

[0051] Preparation of positive electrode sheet: positive electrode material: CNT: PVDF are mixed in a mass ratio of 96:1:3, coated on a current collector, dried, and rolled to obtain positive electrode sheet 3.

[0052] Preparation of negative electrode materials: Preparation of negative electrode materials: 1) Dissolve 169 mg of zirconium chloride solution (ZrCl4) and 121 mg of 1,4-phthalic acid (H2BDC) in a mixed solution of 28 ml of DMF, place in a reactor and heat at 150°C for 12 h, collect the product by centrifugation, and wash it three times with DMF and methanol to obtain a MOF precursor.

[0053] 2) Add 50 ml of styrene to the MOF precursor and sonicate for 30 minutes to obtain a MOF suspension.

[0054] 3) 200 mg of 4-formylphenylboronic acid (FPBA) and 150 mg of 1,3,5-tri(4-aminophenyl)benzene (TAPB) were added twice, poured into a reactor and heated at 120°C for 6 h, then centrifuged. The obtained product was placed in a tubular furnace and heated at 800°C for 12 h to obtain a COF / MOF negative electrode material 1 with high conductivity and high active sites.

[0055] Preparation of negative electrode sheet: negative electrode material 1: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 1.

[0056] Preparation of electrolyte: NaPF6 was dissolved in a mixture of EC:EMC at a mass ratio of 1:1, and 10 wt% FEC was added to obtain the electrolyte.

[0057] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 3, negative electrode sheet 1, electrolyte and separator, and assemble the battery. Battery number is 3. Battery 3 is tested for charge and discharge cycles at 25°C, current 0.5C, voltage 3.0-4.5V, and test data are shown in Figure 1 .

[0058] Example 4

[0059] Preparation of positive electrode material: 1) Put graphite powder into a tube furnace, heat to 1000°C, introduce carbon source gas methane, the flow rate is 1L / min, the reaction time is 30 minutes, and obtain graphene / graphite composite material. 2) Perform ultrasonic dispersion treatment to obtain a uniformly dispersed suspension, the ultrasonic power is 500W, and the ultrasonic time is 2 hours. 3) Pour the suspension into a high-temperature furnace, heat to 2000°C, maintain the pressure at 1atm, and heat treatment time for 1 hour. The graphene / graphite composite material with higher crystallinity and stability is obtained, and then sintered at 1000°C for 5h to obtain positive electrode material 1.

[0060] Preparation of positive electrode sheet: positive electrode material 1: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain positive electrode sheet 1.

[0061] Preparation of negative electrode materials: 1) H2BDC and NH2-H2BDC (3.95 mmol) with a molar ratio of 1:1 were dissolved in 8.32 g of 1M NaOH aqueous solution and stirred for 5 min to obtain solution A. 2.135 g of FeCl3·4H2O was dissolved in 48.6 g of H2O to obtain solution B. After both solutions became completely clear, the diluted solution A was added to solution B under stirring. After stirring at room temperature for 24 h, the products were filtered and washed several times with deionized water and ethanol to remove the residual organic ligands to obtain NH2-MIL-101(Fe)MOF precursor.

[0062] 2) Add 50 ml of styrene to the MOF precursor and ultrasonicate for 30 minutes to obtain a MOF styrene suspension;

[0063] 3) 200 mg of 4-formylphenylboric acid (FPBA) and 150 mg of 1,3,5-tri(4-aminophenyl)benzene (TAPB) were added twice, poured into a reactor and heated at 120°C for 6 h, then centrifuged. The obtained product was placed in a tubular furnace and heated at 800°C (temperature) for 12 h to obtain a COF / MOF negative electrode material 2 with high conductivity and high active sites.

[0064] Preparation of negative electrode sheet: negative electrode material 2: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 2.

[0065] Preparation of electrolyte: NaPF6 was dissolved in a mixture of EC:EMC at a mass ratio of 1:1, and 10 wt% FEC was added to obtain the electrolyte.

[0066] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 1, negative electrode sheet 2, electrolyte and separator, and assemble the battery. Battery number is 4. Battery 4 is tested for charge and discharge cycles at 25°C, current of 0.5C and voltage of 3.0-4.5V. The test data is shown in Figure 1 .

[0067] Example 5

[0068] Preparation of positive electrode material: 1) Put graphite powder into a tube furnace, heat to 1000°C, introduce carbon source gas methane at a flow rate of 1 L / min, and react for 30 minutes to obtain a graphene / graphite composite material.

[0069] 2) Performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension, the ultrasonic power is 500 W, and the ultrasonic time is 2 hours.

[0070] 3) Pour the suspension into a high-temperature furnace, heat to 2000°C, maintain the pressure at 1 atm, and heat treat for 1 hour to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 1000°C for 5 hours (time, temperature) to obtain positive electrode material 1.

[0071] Preparation of positive electrode sheet: positive electrode material: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain positive electrode sheet 1.

[0072] Preparation of negative electrode materials:

[0073] 1) Mix 74.79 mL of aqueous ammonia containing 7.96 g of Zn(NO3)2·6H2O and 80 mL of DMF containing 4.4 g of 2-methylimidazole, stir at room temperature for 2 h to obtain a white suspension, and heat the suspension at 350 r·min. -1 The mixture was stirred at a speed of 1 h, and then centrifuged, washed, and dried to remove the residual organic ligands to obtain a ZIF-8 MOF precursor;

[0074] 2) Add 50 ml of styrene to the MOF precursor and ultrasonicate for 30 minutes to obtain a MOF styrene suspension;

[0075] 3) 200 mg of 4-formylphenylboric acid (FPBA) and 150 mg of 1,3,5-tri(4-aminophenyl)benzene (TAPB) were added twice, poured into a reactor and heated at 120°C for 6 h, then centrifuged. The obtained product was placed in a tubular furnace and heated at 800°C for 12 h to obtain a COF / MOF negative electrode material 3 with high conductivity and high active sites.

[0076] Preparation of negative electrode sheet: negative electrode material 3: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 3.

[0077] Preparation of electrolyte: NaPF6 was dissolved in a mixture of EC:EMC at a mass ratio of 1:1, and 10 wt% FEC was added to obtain the electrolyte.

[0078] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 1, negative electrode sheet 3, electrolyte and separator, and assemble the battery. Battery number is 5. Battery 5 is tested for charge and discharge cycles at 25°C, current of 0.5C and voltage of 3.0-4.5V. The test data is shown in Figure 1 .

[0079] Comparative Example 1

[0080] Preparation of positive electrode sheet: Graphite: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain a positive electrode sheet 4.

[0081] Preparation of negative electrode sheet: negative electrode material 1: CNT: PVDF is coated on the current collector in a mass ratio of 8:1:1, dried and rolled to obtain negative electrode sheet 1.

[0082] Preparation of electrolyte: Add 10% FEC to prepare sodium ion electrolyte according to NaPF6 in EC:EMC=1:1.

[0083] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 4, negative electrode sheet 1, electrolyte and separator, and assemble the battery. Battery number is 6. Battery 6 is tested for charge and discharge cycles at 25°C, current 0.5C, voltage 3.0-4.5V, and test data are shown in Figure 1 .

[0084] Comparative Example 2

[0085] Preparation of positive electrode sheet: positive electrode material 1: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain positive electrode sheet 1.

[0086] Preparation of negative electrode sheet: Graphite: CNT: PVDF is coated on a current collector in a mass ratio of 8:1:1, dried, and rolled to obtain a negative electrode sheet 4.

[0087] Preparation of electrolyte: Add 10% FEC to prepare sodium ion electrolyte according to NaPF6 in EC:EMC=1:1.

[0088] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 1, negative electrode sheet 4, electrolyte and separator, and assemble the battery. Battery number is 7. Battery 7 is tested for charge and discharge cycles at 25°C, current of 0.5C and voltage of 3.0-4.5V. The test data is shown in Figure 1 .

[0089] Comparative Example 3

[0090] Preparation of positive electrode sheet: Graphite: CNT: PVDF are mixed in a mass ratio of 96:2:2, coated on a current collector, dried, and rolled to obtain a positive electrode sheet 4.

[0091] Preparation of negative electrode sheet: Graphite: CNT: PVDF is coated on a current collector in a mass ratio of 8:1:1, dried, and rolled to obtain a negative electrode sheet 4.

[0092] Preparation of electrolyte: Add 10% FEC to prepare sodium ion electrolyte according to NaPF6 in EC:EMC=1:1.

[0093] Battery preparation: Assemble button cells in a glove box, assemble positive electrode sheet 4, negative electrode sheet 4, electrolyte and separator, and assemble the battery. Battery No. 8. Battery 8 was tested for charge and discharge cycles at 25°C, current 0.5C, voltage 3.0-4.5V, and test data are shown in Figure 1 .

[0094] It should be noted that the comparative examples and embodiments of the present application are only for the convenience of comparison, and the comparative example is also a type of embodiment.

[0095] Table 1 shows the conductivity results of Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3. It can be seen from Table 1 that the conductivity of Example 1 is higher than that of Example 2, Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3, indicating that the prepared material can improve the conductivity of the battery.

[0096] Table 2 shows the energy density of the batteries of Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2 and Comparative Example 3. It can be seen from Table 2 that the energy density of Example 1 is much higher than that of the other examples and comparative examples, indicating that the prepared positive and negative electrode composite materials can improve the energy density.

[0097] Table 3 shows the interface resistance of the batteries of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, which is consistent with the conductivity in Table 1, and once again proves the good conductivity of Example 1.

[0098] Figure 1 The cycle performance comparison of batteries 1-8 shows that the cycle performance of battery No. 1 is the best, indicating that only when graphene / graphite is used as the positive electrode and COF / MOF composite material is used as the negative electrode, the electrical performance is the best, and the performance of MOF type NH2-UiO-66 is the best. This solution invented by the present technology can not only reduce the use of graphite and improve the conductivity, but also reduce costs and facilitate operation.

[0099] Table 1 Comparison data of conductivity of the embodiments of the present invention and the comparative examples

[0100] sample Conductivity S / cm Example 1 0.37 Example 2 0.11 Example 3 0.09 Example 4 0.22 Example 5 0.15 Comparative Example 1 0.06 Comparative Example 2 0.028 Comparative Example 3 <![CDATA[10 -6 ]]>

[0101] Table 2 Energy density of batteries in the embodiments of the present invention and comparative examples

[0102] sample Energy density (Wh / kg) Example 1 156 Example 2 145 Example 3 142 Example 4 140 Example 5 144 Comparative Example 1 136 Comparative Example 2 130 Comparative Example 3 113

[0103] Table 3 Interface resistance data of the embodiments of the present invention and the comparative examples

[0104]

[0105]

[0106] In summary, the present invention optionally uses COF / MOF composite materials as negative electrode materials: COF / MOF composite materials have high structural stability and electronic conductivity, which can effectively improve the energy density and power density of the battery. At the same time, the porous structure of the COF / MOF composite material can provide a large number of active sites, which is conducive to the storage and transmission of electrolytes, and solves the safety problems of metal dendrites and capacity attenuation faced by dual-ion batteries.

[0107] Graphene / graphite composite materials can be used as positive electrode materials: Graphene / graphite has high electrochemical activity and stability, which can effectively improve the energy density and power density of the battery. At the same time, the layered structure of graphene / graphite is conducive to the transmission of electrons, which can further improve the electrochemical performance of the battery.

[0108] As a preferred form, COF / MOF with high conductivity and good chemical stability is used as the negative electrode material, and the modified graphene / graphite composite material is used as the positive electrode and assembled with the electrolyte and the separator. The process is simple and safe, the conductivity is high, and the rate performance, cycle performance and energy density are significantly improved.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that: It is a COF / MOF composite material; it includes a MOF core and a COF layer coated on the surface of the MOF core.

2. The negative electrode material according to claim 1, characterized in that The MOF is one of NH2-UiO-66, NH2-MIL-101(Fe), or ZIF-8.

3. The negative electrode material according to claim 1, characterized in that The COF layer is prepared from 4-formylphenylboric acid and 1,3,5-tri(4-aminophenyl)benzene; preferably, the mass ratio of 4-formylphenylboric acid to 1,3,5-tri(4-aminophenyl)benzene is 3:1-3.5:1; preferably 3:

1.

4. A method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: 1) preparing a MOF precursor; preferably, the preparation is carried out in the following manner: adding an M salt and a ligand to a solvent, and collecting a centrifugal product after the reaction; preferably, the M salt is one of a Zr salt, an Fe salt, and a Cu salt; the ligand is one of phthalic acid, 2-aminoterephthalic acid, or 2-methylimidazole; the molar ratio of the M salt to the ligand is 1:1-1.5:1; preferably 1:1; 2) Add styrene to the MOF precursor to obtain a MOF styrene suspension; 3) 4-formylphenylboronic acid and 1,3,5-tri(4-aminophenyl)benzene are added to the MOF styrene suspension and heated for reaction; preferably, the heating temperature is 70-150° C. and the reaction time is 10-24 h; 4) After the reaction is completed, the centrifugal product is further heated to obtain the negative electrode material; preferably, the heating temperature is 120° C. and the reaction time is 12 h.

5. A negative electrode sheet, characterized in that: It comprises the negative electrode material, negative electrode conductive agent and negative electrode binder as described in any one of claims 1 to 3; preferably, the negative electrode conductive agent is CNT; the negative electrode binder is PVDF; preferably, the mass ratio of the negative electrode material, the negative electrode conductive agent and the negative electrode binder is 8:1:

1.

6. A method for preparing a positive electrode material, characterized in that: The following steps are adopted: 1) putting graphite powder into a tube furnace, heating to 800-1000° C., introducing carbon source gas; preferably, the carbon source gas is methane; the flow rate is 1-3 L / min, and the reaction time is 30-60 minutes to obtain a graphene / graphite composite material; 2) performing ultrasonic dispersion treatment to obtain a uniformly dispersed suspension; preferably, the ultrasonic power is 500 W and the ultrasonic time is 2 hours; 3) Pour the suspension into a high temperature furnace, heat to 1500-2000°C, maintain the pressure at 0.5-1atm, and heat treat for 1-2 hours to obtain a graphene / graphite composite material with higher crystallinity and stability, and then sinter at 800-1000°C for 1-5h to obtain a positive electrode material.

7. A positive electrode material, characterized in that: It is a graphene / graphite composite material obtained by the preparation method described in claim 6.

8. A positive electrode sheet, characterized in that: It comprises the positive electrode material, positive electrode conductor and positive electrode binder as described in claim 7; preferably, the positive electrode conductor is CNT; preferably, the binder is PVDF; preferably, the mass ratio of the positive electrode material, the positive electrode conductor and the positive electrode binder is (96-97):(1-3):(1-3); preferably 96:2:

2.

9. A battery, characterized in that: It comprises the negative electrode sheet, positive electrode sheet and separator as described in claim 5; preferably, the positive electrode sheet is the positive electrode sheet as described in claim 8; preferably, the battery is a sodium-based dual-ion battery.

10. A method for preparing a battery according to claim 9, characterized in that: The following steps are adopted: a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator are assembled into a battery; preferably, the electrolyte is NaPF6 dissolved in a mixed solution of EC:EMC at a mass ratio of 1:1, and 10wt% FEC is added to obtain the configuration.